Frieren : beyond journey's end. Volume 3 - Yamada, Kanehito (Viz Media, LLC, 2022)
"Elf mage Frieren and her courageous fellow adventurers have defeated the Demon King and brought peace to the land. But Frieren will long outlive the rest of her former party. How will she come to understand what life means to the people around her? An old enemy returns as Frieren continues her journey north. Decades ago, Frieren and her party defeated a servant of the Demon King called Aura the Guillotine, one of the powerful demons known as the Seven Sages of Destruction. Now Aura is back with a score to settle. But what price did Frieren pay for victory in the past, and how will the choices she made then affect the present?" -- Page [4] of cover.